The Management Productivity Multipliers - Kraines, Gerald (Ascent Audio, 2021)
In his work consulting to major corporations for more than thirty years, Gerald Kraines consistently hears that 60-70 percent of business organizations' potential effectiveness goes unrealized. He shares how to engage, align, and develop employees in order to leverage and encourage optimal performance and long-lasting results. Filled with useful anecdotes and lively case studies, this book will help you increase your wisdom about colleagues, direct reports, and others, as well as yourself. You'll discover how to develop powerful, yet straightforward strategies for leading people more effectively; establish accountability leadership at every level of the organization that adds value; define and implement managerial practices that will fully use people's potential; and drive organizational change and create a culture of adaptive readiness. Business leaders who follow the principles in this book can multiply their chance of success and win back unrealized potential. Accountability, leadership, organizational alignment, and human resource systems are the building blocks for creating productive organizations. Kraines shares clear examples on how to get each of them right and properly integrated into a cohesive whole.